An integrative review exploring black men of African and Caribbean backgrounds, their fears of prostate cancer and their attitudes towards screening. Issue 2 (9th February 2018) - Alexis, Obrey; Worsley, Aaron
Abstract: Evidence suggests that black men are disproportionately more affected than any other ethnicity by prostate cancer. The aim of this review is to identify studies exploring black men of African and Caribbean descent, their fears of prostate cancer and their attitudes towards screening. Four databases were searched and reference lists of relevant papers were hand searched. The inclusion criteria were studies exploring attitudes towards screening and fear of prostate cancer in black men of African and Caribbean backgrounds, peer-reviewed research, qualitative studies, surveys, questionnaires and English language publications. Qualitative findings were synthesized using a thematic framework to which quantitative findings were integrated. Of the 16 papers, 10 were quantitative and 6 were qualitative, all of which were conducted in the United States of America. Poorer and less educated black men were reluctant to seek help for prostate cancer. They may not visit their doctors for fear of intrusion into their personal lives. Moreover, they were fearful of being emasculated as a result of the digital rectal examination. The review identifies a paucity of UK literature on black men's fears and perceptions of prostate cancer. Further studies are needed in the United Kingdom to address this gap in the literature.